MAIN PRINCIPLES AND APPROACHES TO THE FORMATION OF LANDSCAPE DESIGN IN THE REPUBLIC OF KARAKALPAKSTAN (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article is dedicated to the formation of sustainable landscape design principles in the arid climate conditions of the Republic of Karakalpakstan. The study analyzes local plant species, water-saving technologies, and the principles of adapting international experience to regional conditions. Additionally, recommendations have been developed to reduce soil erosion, improve the microclimate, and enhance urban green spaces through green walls and ecological infrastructure. This article proposes approaches aimed at restoring ecological balance and ensuring urban development.